2020
DOI: 10.1530/joe-19-0393
|View full text |Cite
|
Sign up to set email alerts
|

Anti-insulin resistance effects of salidroside through mitochondrial quality control

Abstract: Mitochondrial quality control (MQC) and function are determinants for cellular energy metabolism, and their disorders are reported to play an important role in the development of insulin resistance (IR). Salidroside was reported to have beneficial effects on MQC through AMPK pathway; however, it is unknown whether salidroside exerts anti-IR effect with this action. This study sought to investigate the effects of salidroside on IR with an exploration of the mechanisms of its action. Experimental IR models were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…10 The autophagy process is dependent on a multitude of signaling pathways. Adenosine monophosphate activated protein kinase (AMPK) functions as a regulator of cell energy metabolism, [12][13][14] and phosphorylated AMPK (pAMPK) plays a key role in autophagy. 15 Mammalian target of rapamycin (mTOR), as one of the main autophagy inhibitory pathways, also plays an important role in the occurrence of autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…10 The autophagy process is dependent on a multitude of signaling pathways. Adenosine monophosphate activated protein kinase (AMPK) functions as a regulator of cell energy metabolism, [12][13][14] and phosphorylated AMPK (pAMPK) plays a key role in autophagy. 15 Mammalian target of rapamycin (mTOR), as one of the main autophagy inhibitory pathways, also plays an important role in the occurrence of autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…It ameliorates muscle atrophy in cachexia or denervation via activating mTOR signaling pathway or reducing expression of atrogenes, such as MuRF1 and Atrogin-1 (Chen et al, 2016;Wu et al, 2019). Our previous study also indicated that salidroside resists metabolic disorders in skeletal muscle via upregulating SIRT1-mediated mitochondrial quality control in mice (You et al, 2020). Our present study further showed that in skeletal muscle cells, salidroside abated palmitate-induced SIRT1 inhibition, atrogenes activation, and myotubes atrophy and these therapeutic effects were significantly attenuated by additional EX-527 pre-treatment.…”
Section: Discussionmentioning
confidence: 92%
“…reported that SAL alleviated glucosamineā€induced insulin resistance in HepG2 cells in a doseā€dependent manner [39] . In addition, SAL was found to reduce insulin resistance and regulate mitochondrial quality control and ROS production by activating AMPK/silent information regulator 1 (SIRT1) signaling pathway [40] …”
Section: Pharmacological Activity and Mechanism Of Sal Against Metabolic Diseasesmentioning
confidence: 99%
“…[39] In addition, SAL was found to reduce insulin resistance and regulate mitochondrial quality control and ROS production by activating AMPK/silent information regulator 1 (SIRT1) signaling pathway. [40]…”
Section: Effect Of Sal On Insulin Resistancementioning
confidence: 99%